Arachnoid Cyst in the Middle Cranial Fossa Presenting with Pulsatile Exophthalmos: Case Report and Literature Review - SAITO, Atsushi (Neurol Med Chir (Tokyo), 2014)
A 20-year-old woman suffered gradual progression of right pulsatile exophthalmos and slight headache. Computed tomography (CT) demonstrated outward and downward displacement of the right globe and an arachnoid cyst in the right middle cranial fossa associated with thinned and anterior protrusion of a bony orbit. Microscopic cystocisternotomy was performed and the cerebrospinal fluid (CSF) inside of the cyst communicated into the carotid cistern and cistern in the posterior cranial fossa. Pulsatile exophthalmos improved immediately after surgery. Arachnoid cyst in the middle cranial fossa presenting with exophthalmos is rare. Microscopic cystocisternotomy might successfully improve CSF flow and relieve exophthalmos.